Spatio-temporal genetic variation of juvenile smooth hammerhead sharks in South Africa. Issue 10 (26th November 2019) - Kuguru, Gibbs; Gennari, Enrico; Wintner, Sabine; Dicken, Matthew L.; Klein, Juliana D.; Rhode, Clint; Bester-van der Merwe, Aletta E.
ABSTRACT: The smooth hammerhead shark Sphyrna zygaena is known to display a high degree of site fidelity to specific areas along the South African coastline. This species is vulnerable to overfishing and steep declines have been noted globally. In this study, a dual marker approach was used to investigate the spatial and temporal genetic variation of juvenile S. zygaena across the south and east coast of South Africa. Kinship of individuals was determined within and across cohorts from juvenile S. zygaena sampled in Mossel Bay, a putative pupping ground. Significant genetic differentiation (supported by F-statistics, multivariate analysis and Bayesian clustering) was evident between individuals sampled from the warm temperate south coast and the subtropical east coast, with asymmetric gene flow between regions. Distinct genetic composition was also revealed between sampling years, with different levels of relatedness within and among cohorts, indicating different temporal populations utilizing Mossel Bay annually. Based on these results, further investigation of S. zygaena populations across a wider region is warranted in order to make recommendations regarding conservation management of this vulnerable coastal shark.